Growth, modelling and remodelling of cardiac tissue: a multiphase approach - Hopkins, Gary (Computational Continuum Mechanics Research Group (CCM), 2017)
Rheumatic heart disease (RHD) is identified as a serious health concern in developing countries, specifically amongst young individuals, accounting for between 250 000 and 1.4 million deaths annually. As such, the attention of this research is initially placed on the importance of the development of a cardiac analysis toolbox with functionality for pathophysiological analysis of the disease. Subsequently, in order to further the understanding of the mechanisms of the disease as linked to cardiomyocyte growth and remodelling of the microstructure, a continuum bi-phasic model applicable to cardiac tissue is formulated based on the theory of porous media (TPM). This makes it possible to account for interactions and contributions of multiple phases of constituent materials, which in computational cardiac modelling are the solid phase - the cardiac tissue - and the liquid phase - blood and interstitial uid. Subsequent attention is paid to the cardiac model development in order to implement a sound base on which to add strain-driven phase transition via a mass supply function proposed within this study. To this end, based on thermodynamical restrictions, constitutive relations are proposed for stress, permeability, seepage velocity, mass supply and interaction forces such as friction. The approach is implemented in the in-house computational cardiac mechanics toolbox SESKA which supports finite element as well as Element- free Galerkin-based approximations. This investigation considers the passive and active non-linear elastic material behaviour of the myocardium of the left ventricle coupled with porous media theory, along with an an additional coupling to the haemodynamics of the circulatory system, facilitating modelling of the full cardiac cycle. As such, an initial cardiac growth and remodelling computer model is developed as an initial step to computational modelling of the adverse effects of RHD and other similar in ammatory heart diseases, with the potential to limit the invasiveness and risk of in-vivo patient studies. A patient specific case study is conducted, making use of cardiovascular magnetic resonance scans taken over a period of two years from a patient affected by RHD to generate realistic 3D computer models, from which information is drawn with regards to the pathophysiological behaviour of the disease.